2001
DOI: 10.1063/1.1398543
|View full text |Cite
|
Sign up to set email alerts
|

Overview: Unsolved problems of noise and fluctuations

Abstract: Noise and fluctuations are at the seat of all physical phenomena. It is well known that, in linear systems, noise plays a destructive role. However, an emerging paradigm for nonlinear systems is that noise can play a constructive role-in some cases information transfer can be optimized at nonzero noise levels. Another use of noise is that its measured characteristics can tell us useful information about the system itself. Problems associated with fluctuations have been studied since 1826 and this Focus Issue b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Both games of chance and games of strategy are currently finding increasing applications in physics (Abbott 2001;Abbott et al 2002) and econophysics (Johnson et al 2003).…”
Section: (B) Motivationmentioning
confidence: 99%
“…Both games of chance and games of strategy are currently finding increasing applications in physics (Abbott 2001;Abbott et al 2002) and econophysics (Johnson et al 2003).…”
Section: (B) Motivationmentioning
confidence: 99%
“…[12,[16][17][18][19][20]. However, Parrondo's games have gained particular attention because: (i) they are the first game-theoretic realization of such processes, (ii) in their original form, they can be directly mapped onto the workings of a flashing Brownian ratchet and (iii) the effect is strikingly counterintuitive and relatively simple to analyze.…”
Section: Introductionmentioning
confidence: 99%
“…Noise and fluctuations are ubiquitous to all physical phenomena and is a multidisciplinary field of study (Abbott 2001). The roots of noise research trace back to the Scottish botanist Robert Brown who observed fluctuating pollen on the surface of a film of water in 1822.…”
Section: /F Noise In Physical Phenomenamentioning
confidence: 99%
“…The roots of noise research trace back to the Scottish botanist Robert Brown who observed fluctuating pollen on the surface of a film of water in 1822. The first unsolved noise problem was to find out the origin of Brownian motion (Abbott 2001).…”
Section: /F Noise In Physical Phenomenamentioning
confidence: 99%